Lymphatic filariasis among the Yakurr people of Cross River State, Nigeria - Iboh, Cletus I (BioMed Central, 2012)
BACKGROUND: In order to initiate a disease elimination programme for lymphatic filariasis based on mass drug administration, a proper understanding of the geographical distribution and degree of risk is essential. METHODS: An investigation of lymphatic filariasis due to Wuchereria bancrofti was carried out among 785 people in four communities of Yakurr Local Government Area of Cross River State, Nigeria between March and August, 2009. Finger prick blood smear samples collected from the subjects were examined for W. bancrofti using standard parasitological protocol. The subjects were also screened for clinical manifestations of lymphatic filariasis. RESULTS: Of the 785 persons examined, 48 (6.1%) were positive for microfilariae in their thick blood smear. There was a significant difference in the prevalence of lymphatic filariasis among the various age groups (P < 0.01) although peak prevalence occurred between 41 – 60 years. There was no significant difference in prevalence and density with respect to sex (P > 0.05). The overall mean microfilarial density of the infected individuals was 5.6mf/50 μl. There was a significant variation (P < 0.01) in mean microfilarial density within the communities, ranging from 4.7 to 6.4 mf/50 μl. The only clinical sign found in the study area was lymphoedema of the leg recording 2 (0.3%) prevalence. CONCLUSIONS: The National Lymphatic Filariasis Elimination Programme should intervene by expanding the distribution of albendazole and ivermectin to all endemic areas including Yakurr Local Government Area of Cross River State, Nigeria.